Offline exhaled nitric oxide in children: chemiluminescence vs. electrochemical devices - Wilmer A. Madrid; Carlos Guzmán-Valderrábano; David Martínez-Briseño; Luis Torre-Bouscoulet; David H. Ramírez-San Juan; Laura Gochicoa-Rangel (Permanyer, 2021)
Background: Exhaled nitric oxide (eNO) is a noninvasive marker of airway inflammation that has been used in children, using the "offline" technique. To the extent of our knowledge, no article reported in literature compares the concordance and correlation between the two different technologies used to measure eNO at tidal volume offline. This study aimed to report the concordance and correlation of the eNO measured "offline" at tidal volume, using chemioluminiscence (cl) vs electrochemical devices (eq). Methods: A cross-sectional, observational, and prospective study was conducted in the National Institute of Respiratory Diseases (Instituto Nacional de Enfermedades Respiratorias), Mexico City. Healthy children and those with a lung disease between 1 and 11 years of age were included. The exhaled air sample at tidal volume was obtained by attaching a mask connected to a Mylar® bag. Results: We studied 36 children. The mean ± standard deviation (SD) age of the study population was 6 ± 2.6 years; 25% of the subjects included were healthy, and the rest had a lung disease. The concordance correlation coefficient between the two measuring devices was 0.98 (p < 0.001), with a mean difference of 1.46 ± 3.5 ppb and 95% limits of agreement from -5.3 ppb to 8.3 ppb. The linear regression model equation for the estimation of eNO was eNOcl = (eNOeq·1.0718) - 0.1343 (r2 = 0.97). Conclusions: The measurement of eNO at tidal volume by the offline method can be analyzed by electrochemical devices, and the results are interchangeable with those analyzed by chemiluminescence technology.